(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Catalytic combustion, in which fuel is oxidized with the help of a catalyst, has been tested in spark-ignition engines and has been found to increase thermal efficiency and decrease exhaust pollutants. The price of crude oil and other petroleum products is expected to skyrocket and scarcity to persist throughout the 21st century. However, the massive increase in vehicle numbers has begun dictating fuel requirements. Diesel and petrol are becoming increasingly scarce and expensive. As fossil fuels are used up, new technologies that utilize these fuels will become increasingly commonplace over the next few decades. In this experiment, butanol is used instead of petrol. In a spark ignition (S.I.) engine, scavenging is the primary combustion-related issue. This research comprises copper coated piston and Butanol-gasoline blends to evaluate performance and exhaust emissions of two-stroke engine. In this work an effort is made to explore the effect of the piston top coated with catalytic materials such as copper utilizing plasma spray cannon. Two-stroke, single-cylinder, spark ignition (SI) engines with butanol petrol blends are tested experimentally to assess their performance and exhaust pollutants. Piston crowns with a composition of 90% petrol and 10% butanol by volume, 80% petrol and 20% butanol by volume, or 70% petrol and 30% butanol by volume have a 300 micron thick Copper coating. The achieved outcomes are compared to those of a standard S.I engine running on petrol alone. Brake thermal efficiency, Mechanical efficiency, Brake specific fuel consumption, and exhaust emissions like carbon monoxide (CO) and un-burned hydro carbons (UBHC) are only some of the performance metrics that may be determined by subjecting the engine to varying degrees of work. When compared to a typical engine running on pure petrol, one that uses a blend of butanol and petrol achieves greater performance and lower pollution levels. The results of this study show that, when compared to all other fuel blends including petrol, blend B10 (10% Butanol & 90% Petrol by Vol) provides the best performance and emission results.